Estimating population relation- method and assumptions - Sapkota, Vishnu Prasad (Health Prospect, 2014)
Researchers often try to estimate the relationship among the variables in a population using regression modelling. In public health statistical literature, a clear theoretical introduction about the theory underlying the estimation techniques and assumptions is often lacking. In empirical papers, many do not discuss the violation of regression assumptions, and quite often, emphasis has been laid only on the aspects that are less important. In this theoretical review, I have described a theory behind the estimation of population relation, preliminaries of regression methods and various assumptions one has to take care of while estimating the population relation in an unbiased manner. DOI: http://dx.doi.org/10.3126/hprospect.v13i1.11105 Health Prospect Vol.13(1) 2014: 4-6